Ila Mamati's Prayer Method of Memorizing the Al-Qur’an at High School at the Tahfidzul Qur'an Islamic Boarding School, Nurul Istiqalal Wonosari Klaten - Luthfi Badrus Tsani; Fauzi Muharom (al-Afkar, Journal For Islamic Studies, 2025)
Prayer ila mamati is a phrase taken from Arabic. Sholati means my prayer, ila means until, while mamati means my death. So "my prayers until my death" means that I, as a memorizer of the Qur'an, have the responsibility to uphold both obligatory and sunnah prayers, try to be istiqamah and muraja'ah of the Qur'an in sunnah prayers until I die. Tahfidul Qur'an Nurul Istiqlal Islamic Boarding School Wonosari Klaten is a non-formal educational institution whose address is Pandanan Village, Wonosari District, Klaten Regency, Central Java Province. This article is included in qualitative research with a type of approach, namely literature study. In the literature study, researchers carried out activities to collect literature related to the ila mamati prayer method in facilitating memorization of the Al-Qur'an. This research uses books and other literature as the main object. So the type of research used is qualitative research. The implementation of the shalati ila mamati method is carried out when we pray. Because in prayer we definitely read the verses in the Koran, both short and long verses. However, this method is prioritized during sunnah prayers. The principles of the Illa Mamati prayer method are as follows: the principle of motivation, the principle of having the Al-Qur'an memorized, the principle of istiqomah. Applying a learning method in a learning activity is not as easy as imagined, especially in memorizing the Al-Qur'an. Sometimes how it happens and the reality that we find when we go directly into the field does not match what is expected with the theory learned when using this learning method. In every implementation or implementation there are definitely inhibiting and supporting factors that influence the use of the method, as well as when implementing it.